2015
DOI: 10.1016/j.actatropica.2015.03.024
|View full text |Cite
|
Sign up to set email alerts
|

A survey of intestinal parasites including associated risk factors in humans in Panama

Abstract: The preliminary data obtained in the current study, showing a high prevalence of fecal-oral transmitted parasites in Panama, place intestinal parasitism as a major health problem in this country. Specific interventions should be planned for the indigenous population, the group most afflicted by intestinal parasites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
2
9
0
3
Order By: Relevance
“…Studies including the general population can analyze the interplay between poverty, age and parasitism. This study corroborates findings of G. intestinalis among children 13 , 29 . Kiani et al 31 detected an inverse relationship between IPIs and age; however, in their study the role of age as a predictor for IPIs may have been confounded by employment, as detected with E. nana in this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Studies including the general population can analyze the interplay between poverty, age and parasitism. This study corroborates findings of G. intestinalis among children 13 , 29 . Kiani et al 31 detected an inverse relationship between IPIs and age; however, in their study the role of age as a predictor for IPIs may have been confounded by employment, as detected with E. nana in this study.…”
Section: Discussionsupporting
confidence: 91%
“…To our knowledge, this is the first epidemiological study on IPIs conducted in this large urban center. Current public policies and international guidelines related to IPIs focus almost exclusively on soil transmitted helminths (STH) 10 - 12 , however, many recent studies have found a shift in community profiles of IPIs from a predominance of STH to protozoans 13 - 16 . Therefore, this cross-sectional study, following the Strengthening the Reporting of Observational Studies in Epidemiology Guidelines (STROBE), assessed the socioenvironmental conditions and prevalence of IPIs in slums of Rio de Janeiro, RJ State, Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Continued exposure to these factors is important for maximizing the parasitic burden and, therefore, the development of intestinal parasites. It is worth noting that the very same conditions are predisposing factors of polyparasitism [3,5,17], as observed in our study.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, risk factors for the development of enteroparasitosis include contact with residues of different natures and water contaminated with human faeces, inadequate housing conditions, poor hygiene practices, low education, and family income [3,5]. Continued exposure to these factors is important for maximizing the parasitic burden and, therefore, the development of intestinal parasites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation